New approaches to early detection of polycystic ovary syndrome in obese women - Artyomenko, V.V.; Velychko, V.I.; Lahoda, D.O. (REPRODUCTIVE ENDOCRINOLOGY, 2022)
Objectives: development of an algorithm for the early detection of comorbid pathology polycystic ovary syndrome (PCOS) in obese women. Materials and methods. The study included 56 women aged 28.02 ± 2.25 years with a diagnosis of obesity who had no history of PCOS. The examination was carried out by a multidisciplinary group of doctors consisting of a family doctor, a gynecologist and an endocrinologist. The patient’s history of life and diseases was studied, an anthropometric еxamination and a survey according to the modified Ferriman–Gallwey scale were performed with a further ultrasound examination and a gynecologist consultation. Results. The majority of patients (55.36%) had acne, hirsutism and seborrhea occurred in 41.07 and 26.76% of women, respectively, and 14.29% of patients had alopecia. Often, the patient had not one, but several symptoms at the same time. According to the modified Ferriman–Gallwey scale, the majority of women (58.92%) had no manifestations of hirsutism along with obesity, 17.8% had moderate manifestations of hirsutism, 16.07 and 7.14% had mild and moderate hirsutism, respectively. The patients had no complaints and did not know whether they had PCOS. PCOS were diagnosed in 31 (55.36%) women after ultrasound examination and gynecologist consultation. It was also found that patients with longer obesity and a higher body mass index were more likely to have a diagnosis of PCOS (ρ = 0.77). The largest number of PCOS patients was among women with a body mass index over 40 kg/m2, i.e. with the III degree of obesity. Conclusions. The algorithm we developed for the diagnosis of PCOS in obese patients allowed us to detect this disease early in 55.36% of cases. We consider it appropriate to recommend screening for PCOS to all obese patients of reproductive age. This tactic will help maintain the fertility of this category of patients.